Literary Grammar: The Grammaticalization of the Hebrew Wayyiqṭol in Typological Comparison with the Classical Japanese Kakari-Musubi, the Old Irish Dependent Conjugation, and the Tocharian Gendered 1st Person Singular Pronoun - Wikander, Ola (Scandinavian journal of the Old Testament, 2020)
In this article, the grammaticalization and narrative use of the Hebrew wayyiqṭol form is discussed in typological comparison with three phenomena from non-Semitic (and, indeed, non-Afro-Asiatic) languages: the so-called Kakari-musubi of Classical Japanese, the dependent conjugation of Old Irish, and the masculine/feminine distinction of the first person singular pronoun of East Tocharian. These comparisons are used to illustrate relations between particles and forms in grammaticalization, the rise of particleinduced morphological variation, and the social role of grammaticalization phenomena, thus providing new clues for the understanding of the rise of the wayyiqṭol as a grammaticalized form going back to the social situation of telling epic, narrative stories.